2015
DOI: 10.1590/1982-0216201519213
|View full text |Cite
|
Sign up to set email alerts
|

Importância da educação formal dos responsáveis e renda familiar no processo de adesão ao uso de próteses auditivas em menores de 12 anos

Abstract: OBJETIVO: verificar se o nível de educação formal dos responsáveis pelas crianças atendidas no serviço de Saúde Auditiva de um Hospital Universitário, assim como a suas rendas familiares e o grau das perdas auditivas das crianças, influencia na adesão ao uso de próteses auditivas. MÉTODOS: foi realizado um estudo retrospectivo por meio de um levantamento de dados secundários contidos em fichas técnicas no Laboratório de Exames Complementares do referido Hospital. Foram verificados os dados sobre o tipo e o gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It was observed that the characteristics of the children in the intervention groups certainly determined the needs for adaptations to be made (Lederberg, Schick, & Spencer, 2013), with emphasis on the time of sensory deprivation (Bornstein, 2018;Wake & Carew, 2016), the restricted use of hearing aids for some of them (Penna, Lemos, & Alves, 2015;Vasconcelos, & Pereira, 2015) and the late entry into the hearing (re)habilitation program (Bicas, Guijo, Delgado-Pinheiro, 2017;Oliveira, Penna, & Lemos, 2015;Tabaquim et al, 2013), which were factors verified in the sample and which should be considered in the development of strategies for phonological work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the characteristics of the children in the intervention groups certainly determined the needs for adaptations to be made (Lederberg, Schick, & Spencer, 2013), with emphasis on the time of sensory deprivation (Bornstein, 2018;Wake & Carew, 2016), the restricted use of hearing aids for some of them (Penna, Lemos, & Alves, 2015;Vasconcelos, & Pereira, 2015) and the late entry into the hearing (re)habilitation program (Bicas, Guijo, Delgado-Pinheiro, 2017;Oliveira, Penna, & Lemos, 2015;Tabaquim et al, 2013), which were factors verified in the sample and which should be considered in the development of strategies for phonological work.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 30 years, surprising technological and scientific advances have given children with hearing impairment access to speech sounds at a time favorable to their language development (Wake & Carew, 2016;Bornstein, 2018). Even so, due to the variables involved in the (re)habilitation process -such as: age at diagnosis, cause and degree of hearing impairment, time of use of hearing aid devices, family involvement in the therapeutic process (Bicas, Guijo, & Delgado-Pinheiro, 2017;Moret, 2017;Oliveira, Penna, & Lemos, 2015;Penna, Lemos, & Alves, 2015;Tabaquim et al, 2013;Vasconcelos & Pereira, 2015), among other factors -, hearing impaired children have a disadvantage in relation to hearing children in terms of phonological processing and are, therefore, a risk population for the acquisition of the ability to read (Goldberg & Lederberg, 2015;Lederberg, Schick, & Spencer, 2013;Naveka von Mentzer et al, 2013;Werfel, Douglas, & Ackal, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…O segundo tratamento mais relatado foi a indicação de aparelho auditivo: que garanta a adesão do sujeito por se sentir pertencente e ver as potencialidades resultantes do processo 74,221 .…”
Section: Aparelho Auditivounclassified
“…A privação sensorial pode ter consequências biológicas, psicológicas e sociais importantes. Estudos relacionam a privação auditiva com isolamento social, ansiedade, depressão e declínio cognitivo 221,222 . Em contextos específicos, como o relatado por Nascimento et al (2017) 223 nas comunidades ribeirinhas da Amazônia, a perda auditiva foi relacionada com a maior ocorrência de mortes, uma vez que nesta população, o conhecimento e as informações são passados prioritariamente de forma verbal, seja pessoalmente, por rádio ou televisão, e foram verificadas que muitas mensagens que incluíam questões relacionadas à sobrevivência da comunidade estavam se perdendo pela dificuldade auditiva de seus membros.…”
Section: Aparelho Auditivounclassified
See 1 more Smart Citation